2021
DOI: 10.3390/medicina57010043
|View full text |Cite
|
Sign up to set email alerts
|

Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS): Major Impact on Lives of Both Patients and Family Members

Abstract: Background and objectives: To explore the impacts that Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS) has on the patient and their family members using the WHOQOL-BREF (Abbreviated World Health Organisation Quality of Life questionnaire) and FROM-16 (Family Reported Outcome Measure-16) quality of life assessments. Materials and Methods: A quantitative research study using postal questionnaires was conducted. A total of 39 adult volunteers expressed an interest in participating in the study: 24 ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 13 publications
(8 reference statements)
0
16
0
Order By: Relevance
“…Most previous studies on the impact on family members of persons with ME/CFS have focused on children with ME/CFS27–29 making comparisons difficult, however in a pilot study, Brittain et al 4 compared the impact of ME/CFS on UK patients and on family members, using WHOQoL-BRef and FROM-16. That study demonstrated that poor QoL of the person with ME/CFS is associated with a high impact on the QoL of family members.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most previous studies on the impact on family members of persons with ME/CFS have focused on children with ME/CFS27–29 making comparisons difficult, however in a pilot study, Brittain et al 4 compared the impact of ME/CFS on UK patients and on family members, using WHOQoL-BRef and FROM-16. That study demonstrated that poor QoL of the person with ME/CFS is associated with a high impact on the QoL of family members.…”
Section: Discussionmentioning
confidence: 99%
“… 2 There is growing international acknowledgement of the impact of ME/CFS on caregivers, 3 but there is only a small scale pilot study, using the Family Reported Outcome Measure (FROM-16) which showed that QoL of partners and other family members is greatly impaired, suggesting that ME/CFS impact goes far beyond the affected person. 4 There is therefore very little information about the partner/family impact, a gap in ME/CFS knowledge which this study aims to address.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The FROM-16 is a family quality of life questionnaire designed to measure the family impact of any disease across all medical specialities, and was developed following interviews of family members of adult and paediatric patients, covering 144 different diagnoses across 26 medical specialities (Golics et al 2013). The FROM-16 has since been used in the eld of urology, to evaluate the family quality of life impact of urinary stone disease (Raja, Wood, and Joshi 2020), and in cancer (Chantarasap et al 2019), COVID-19 (Shah et al 2021) and myalgic encephalitis (Brittain et al 2021). It comprises 16 items in two domains (Emotional, and Personal & Social Life) which ask the participant to state how much they feel their relative's disease has impacted upon that area of their life, with 3 possible responses (0 Not at all, 1 A little, and 2 A lot).…”
Section: Family-reported Outcome Measure-16mentioning
confidence: 99%
“…With regard to the impact of ME/CFS on the quality of life of patients and their families, Brittain et al [22] conducted a quantitative research study using postal questionnaires. Twenty-four adult volunteers responded, indicating that ME/CFS negatively affects the quality of life of the patient.…”
mentioning
confidence: 99%